Influence of hydrothermal aging on the catalytic activity of sulfated zirconia - Busto, Mariana (2008)
The use of reflux aged zirconia gel in the synthesis of sulfated zirconia catalysts for isomerization of short paraffins and isomerization-cracking of long paraffins was assessed. It was found that reflux aging greatly improved zirconia textural properties. The growth of the monoclinic phase was greatly suppressed and the initial area and sintering resistance were increased. The specific surface area of reflux aged material with no sulfate was almost 75 m2 g-1 after calcination at 800 °C. Sulfate promotion of aged materials further increased the tetragonal/monoclinic ratio and the area of sulfated catalysts was 220 m2 g-1 after calcination at 600 °C. Impregnation of reflux aged materials with sulfate produced materials which had very low activity in isomerization of n-butane. The effect of aging was explained in terms of a dissolution-precipitation process that eliminated specific sites of the gel that were responsible for much of the activity of the final catalyst. In the case of the hydroisomerization-cracking of long paraffins the effect was less deletereous partly due to the higher reactivity of this feedstock.